Durable gelfoams stabilized by compressible nanocomposite microgels. Issue 93 (19th October 2022) - Nishizawa, Yuichiro; Watanabe, Takumi; Noguchi, Tetsuya; Takizawa, Masaya; Song, Chihong; Murata, Kazuyoshi; Minato, Haruka; Suzuki, Daisuke
Abstract : Compressible nanocomposite microgels can stabilize the air/water interfaces of gas bubbles for several months, which affords durable gelfoams. Abstract : Although hydrogel microspheres (microgels) are useful as emulsion stabilizers, typical microgels cannot stabilize foams over a prolonged period of time. Here, we found that compressible nanocomposite microgels with solid nanoparticles can overcome undesired desorption of microgels from the air/water interface of bubbles, and form highly durable, microgel-surrounded foams (gelfoams).